Effective Digital Marketing Strategies for Local Fashion Brands Targeting Gen-Z Consumers - Babayeva, Narmin; Lhotáková, Markéta, 1971-; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
In a fiercely competitive global fashion landscape dominated by the fast fashion companies, small scale local fashion brandshave significant challenges to compete and have market presence. This research studies the local fashion brands located in Baku, Azerbaijan by analysing how they can leverage digital marketing strategies to attract Generation Z (Gen-Z) consumers. Gen-Z is the main focus of this research due to being demographic significant for these companies thanks to its strong purchasing power and wide digital presence. Based on a mixed-methods approach, the findings of thesis are formulated primarily based on quantitative data from Gen-Z consumers (through surveys) and qualitative data from local fashion brands’ representatives (through semi-structured interviews). The findings depict that currently, insufficient amount of digital marketing strategies is being utilized by the local fashion companies limited mainly to Instagram Advertisements and Influencer Marketing. However, customer engagement-based strategies such as styling combinations and user-generated content are found to outperform traditional influencer marketing from the consumer perspective due to being perceived more authentic. This key finding paves the way for the comprehensive recommendations for the usage of digital marketing strategies based on secondary and primary research findings within this research. The study also concludes that Instagram, Pinterest and TikTok are the most effective digital media platforms to reach Gen-Z consumers, however, companies’ presence is mostly clustered in Instagram showing a gap and opportunity for active engagement in other platforms as well. Finally, findings also reveal that while Gen-Z in Baku self-reports to be sustainable consumers, their purchasing behaviours are dominated primarily by the fast fashion.
Notwithstanding this attitude-behaviour gap, this study also finds practical examples of their positive reactions to the sustainability actions of the local brands which is promising for the future. This study contributes to both academic literature and practical marketing via identifying the effective digital strategies grounded in primary research findings and theories such as market orientation, brand equity as well as value proposition. The thesis offers a locally significant digital marketing roadmap for the brands in Baku, Azerbaijan.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses